Middling Romanticism : Reading in the Gaps, from Kant to Ashbery - Sng, Zachary, 1971- (Book collections on Project MUSE., 2020)
Examines various forms of the middle (such as the medium, moderation, and mediocrity) that re-negotiated in the writings of British and German romanticism, along with a consideration of how our own relationship to romanticism is influenced by its medial thinking.